Eksistensi Guru PAI dalam Meningkatkan Etika/Moral Siswa di SD Negeri 4 Belanting - Nurhasanah Nurhasanah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
The existence of teachers of Islamic Education in the process of education and learning is an effort to provide the provision of skills to students, whether in the field of cognitive (knowledge), affective (attitude and behavior) and psychomotor (self-actualization and skills) that must be owned. And for a teacher who has the competence both professionally, personally and socially will be able to carry out the teaching well and true in an effort to provide understanding and knowledge and optimal result, especially in improving ethics (moral) or morals learners themselves. Relation to the existence of teachers of Islamic Education in an effort to improve the ethics / moral of learners is explained that the teacher (educator) is the person who assumes the responsibility to guide, where he is not only responsible for delivering learning materials to learners but also responsible for forming keperibadian (morals / morals) protégé of high value. It is further explained that the teacher (educator) is the responsible adult to provide guidance to the learner in his physical and spiritual development in order to achieve maturity, capable of performing his duties as God's creature, khalifatullah, social creature, and as a self-sufficient individual